The ethics of friendship in the Victorian novel - Stallings, CL (2024)
Friendship, in its many forms, comprises the focus of this thesis. The Victorian realist novel provides the site in which enduring philosophical and literary questions pertaining to the role of friendship in the flourishing life are tested, probed, and analysed. Driving this research are the following questions: What did friendship mean to Victorians? How was it conceptualised or theorised in the realist novel and the periodical press? How was friendship understood in everyday life, as evidenced by diction used in personal letters, newspapers, reform movements, and legislation? By means of a methodological coalition, comprised of historicism, gender studies, genre studies, and queer theory, this thesis argues that the Victorian realist novel looked to the articulation of forms of friendship as imaginative solutions to urgent social problems, including Factory Reform, the Woman Question, social mobility, and England’s inadequate and underperforming welfare system. In the wider context of Victorian Studies, this research challenges the symptomatic readings through which representations of friendship in the Victorian novel have often been understood. Eve Kosofsky Sedgwick’s Between Men (1985), which brought questions of friendship to the fore in Victorian Studies in an exciting and new way, is this thesis’s main interlocutor. By expanding Sedgwick’s methodological scope, this thesis demonstrates that Victorians regularly (and consciously) represented and conceptualised friendship as an ethical praxis, expressed through support in times of crisis, financial help, forms of patronage, and working to achieve greater degrees of social justice. It argues that the friendship plot is neither necessarily subservient to or in service of other plots (e.g., the marriage plot) nor primarily an expression of sublimated homosexual desire. Situated within the West’s longer literary–philosophical tradition of friendship writing, this study challenges the established friendship ‘canon,’ from Plato and Aristotle to Derrida, arguing that the Victorian realist novel supplies many of the egalitarian, democratic, inclusive, and politically-minded forms of friendship that Derrida calls for in The Politics of Friendship. The aspiration of this thesis is to begin charting out an avenue by which the Victorian realist novel may be recognised as a critical contributor to persistently important questions about the role of friendship in a flourishing life.